KEBIJAKAN PROTEKSIONISME DOMESTIK DAN KEPATUHAN HUKUM PERDAGANGAN INTERNASIONAL: POLEMIK DAGANG INDONESIA - Nooraini Dyah Rahmawati (Journal of Innovation Research and Knowledge, 2025)
Several controversies have arisen from Indonesia’s efforts to protect local industries in the context of international trade. This article discusses three key issues: the nickel export ban (DS592), subsidies on Chinese products, and sugar import policies. Domestic policies often conflict with WTO regulations and the principles of free trade, such as Articles XI and XX of the GATT and the SCM Agreement. The raw nickel export ban aims to support downstream industrialization but has been challenged by the European Union. Meanwhile, Chinese subsidies pose challenges for local industries, and sugar import policies raise concerns of discrimination. Employing a normative-juridical method, this article examines the importance of strategies that balance domestic protectionist policies with compliance with international trade law, including the application of Article XX of the GATT as justification for domestic policies